Examining complexity in grip selection tasks and consequent effects on planning for end-state-comfort in children with developmental coordination disorder: A systematic review and meta-analysis. Issue 4 (18th May 2020) - Bhoyroo, Ranila; Hands, Beth; Steenbergen, Bert; Wigley, Charles A.
ABSTRACT: This is the first review to provide both a systematic and meta-analytic approach to characterizing motor planning deficits in children with Developmental Coordination Disorder (DCD). Task complexity appears to be a key factor affecting motor planning in children with DCD. However, the different task-related factors and how they affect motor planning ability has not been examined. By systematically reviewing ten studies examining motor planning in children aged 4- to 14 years with and without DCD using grip selection tasks, task complexity was determined according to grip choices, level of precision, number of action steps and degree of rotation. A meta-analysis (N = 607; DCD = 255) revealed that, overall, those with DCD were 6.8% less likely to plan motor actions comfortably than typically developing children. This ability was moderated by task complexity ( I 2 = 66.7%), with performance differences ranging from 2.33% for low ( g = 0.21) to 13.77% ( g = 0.79) for high complexity. The results confirmed that children with DCD are able to plan for comfortable end states for tasks with simple and medium complexity level. When task complexity increased, compared to typically developing children, the motor planning ability of those with DCD was affected to a significantly greater extent. These findings provide important implications for both behavioral and neurological interventions.